Why we lost the sex wars : sexual freedom in the #MeToo era - Bracewell, Lorna N. (University of Minnesota Press, 2021)
"Reexamining feminist sexual politics since the 1970s--the rivalries and the remarkable alliances. Since the historic #MeToo movement materialized in 2017, innumerable survivors of sexual assault and misconduct have broken their silence and called out their abusers publicly--from well-known celebrities to politicians and high-profile business leaders. Not surprisingly, conservatives quickly opposed this new movement, but the fact that "sex positive" progressives joined in the opposition was unexpected and seldom discussed. Why We Lost the Sex Wars explores how a narrow set of political prospects for resisting the use of sex as a tool of domination came to be embraced across this broad swath of the political spectrum in the contemporary United States. To better understand today's multilayered sexual politics, Lorna N. Bracewell offers a revisionist history of the "sex wars" of the 1970s, '80s, and '90s. Rather than focusing on what divided antipornography and sex-radical feminists, Bracewell highlights significant points of contact and overlap between these rivals, particularly the trenchant challenges they offered to the narrow and ambivalent sexual politics of postwar liberalism. Bracewell leverages this recovered history to illuminate in fresh and provocative ways a range of current phenomena, including recent controversies over trigger warnings, the unimaginative politics of "sex-positive" feminism, and the rise of carceral feminism. By foregrounding the role played by liberal concepts such as expressive freedom and the public/private divide as well as the long-neglected contributions of Black and "Third World" feminists, Bracewell upends much of what we think we know about the sex wars and makes a strong case for the continued relevance of these debates today. Why We Lost the Sex Wars provides a history of feminist thinking on topics such as pornography, commercial sex work, LGBTQ+ identities, and BDSM, as well as discussions of such notable figures as Patrick Califia, Alan Dershowitz, Andrea Dworkin, Elena Kagan, Audre Lorde, Catharine MacKinnon, Cherríe Moraga, Robin Morgan, Gayle Rubin, Nadine Strossen, Cass Sunstein, and Alice Walker."--